Pendidikan Berorientasi Pengembangan Bakat, Naluri Dan Fitrah - Chadijah Chadijah; Radjiman Ismail; H.Moh. Natsir Mahmud (Peneliti.net, 2023)
Humans are creatures that have fitrah dimension, namely the dimension of holiness that is inherent in every child from birth to earth. But what distinguishes every human being is the ability to maximize hearing, talent and instinct in the educational process. Therefore, education is needed as a means that can develop the potentials that exist in humans in accordance with the nature of their creation. Then humans are able to play a role and can bring benefits in various aspects of life. The purpose of Islamic education is basically to perfect behavior and cultivate human talents and instincts in harmony with nature.